KETERLIBATAN MORO NATIONALISM LIBERATION FRONT (MNLF) DALAM PERJUANGAN KEMERDEKAAN MUSLIM MORO DI FILIPINA 1971-1996 - Gerry Agung Pranata, - (2021)
The thesis is titled "Moro Nationalism Liberation Front (MNLF) Involvement in the 1971-1996 Moro Muslim Independence Struggle in the Philippines". In general, this research discusses the Moro Nationalism Liberation Front (MNLF) which took place in the Philippines in 1971-1996. The objectives to be achieved in the research are outlined into several questions, namely (1) How was the background of the establishment of the Moro Nationalism Liberation Front in 1971?; (2) What was Nur Misuari's role in building MNLF into an influential front in the Philippines?; (3) What is the impact of MNLF struggle for moro Muslim independence?;. The method used in this research is historical method by doing four steps of research, namely heuristics, criticism, interpretation, and historiography. Based on the results of the study, social and political living conditions in the Philippines are the driving factors of conflict such as ethnic discrimination, social inequality, restrictions on public space for the people, repressive and authoritarian actions displayed by the Philippine government. The efforts made by the Moro Muslims in fighting for independence are to conduct protest movements and resistance movements. The Moro Muslims received discrimination from the government, so the Moro Muslims fought back with resistance with the help of the MNLF under the leadership of Nur Misuari. The MNLF resistance event finally ended peacefully, resulting in a major impact on the changes in social and political life towards a better direction. Keywords: Muslim Moro, MNLF, Nur Misuari